SUFFERING IN EMILY DICKINSON’S SELECTED POEMS - Yusni H., Yusni H.; Suhadi, Jumino; Purwarno, Purwarno (JOURNAL OF LANGUAGE, 2024)
This research examines the theme of suffering in Emily Dickinson’s selected poems, focusing on her unique poetic approach and the profound emotional resonance her work evokes. Emily Dickinson, a pivotal figure in 19th-century American literature, frequently explored themes of death, pain, and existential questions. Despite her reclusive life, her poetry is rich with personal imagery and symbols, reflecting her deep preoccupation with mortality and the human condition. The study utilizes a structural analytical approach, combining library research with descriptive qualitative analysis. This method involves a thorough examination of relevant literary critiques and an in-depth textual analysis of Dickinson’s poems. The aim is to uncover how Dickinson’s portrayal of suffering contributes to a deeper understanding of human experience. Findings indicate that Dickinson’s treatment of suffering is multifaceted, often depicting pain as a necessary aspect of the human soul's development and a precursor to joy and peace. Her poems suggest that pain and suffering are integral to personal growth and resilience. Dickinson’s ability to articulate the complexities of suffering through her innovative use of language and metaphor makes her work both timeless and universally relatable. Overall, Emily Dickinson’s exploration of suffering provides a profound insight into the human experience, highlighting the interconnectedness of pain, joy, and personal growth. Her poetry remains a significant contribution to American literature, offering a nuanced perspective on the inevitability of suffering and its role in shaping the human soul.